African women in traditional religions: illustrations from Kenya - Wangila, Mary N. (Women and new and Africana religions, 2010)
In this chapter, I employ an analytical approach in examination of the status and role of women in indigenous religions of Africa. The objective is to highlight points of comparison in these religion to argue about possible influences and social experience of African women as per the norms in indggenous communities.
free
Keywords: Culture and religion – Kenya; Social status and religion; Women – Kenya; Women – Religious life; Women – Social conditions